Pemanfaatan Check Position Base Transceiver Station oleh Satreskrim dalam Penangkapan Pelaku Tindak Pidana Tadah - Celo, Pedro (Advances in Police Science Research Journal, 2019)
The industrial revolution 4.0 comes characterized by a rapid increase in technology. Public sector organizations such as the police certainly need a method or way to behave towards technological development. One of them is reflected through the Sumedang District Criminal Investigation Unit that utilizes Check Position Base Transceiver Station (BTS) to deal with a Fence, specifically the criminal act of a motor vehicle container. The authors raise the issue that focuses on how to use the Check Position BTS in the arrest of perpetrators of Fencing. The research method in this paper uses a qualitative approach and the type of research is in the form of case studies. On the other hand, the authors took research data located in the Sumedang district police jurisdiction through interview, observation, and literature study techniques. The discussion in this study is divided into 3 (three) sections. First, the Criminal Acts of the Rudiman Ujang Suspect analyzed using Management Information Systems Theory. Seccond, the Stages of Using BTS Check Position are analyzed using the theory of effectiveness theory. Third, Factors that Influence the Use of the Check Position Base Transceiver Station Method In the Arrest of Fencing Criminal Actors consisting of Internal and External Factors. The conclusion of this research explains that BTS Check Position is felt to be very helpful in the performance of the Criminal Investigation Unit. However, there are still some obstacles and constraints such as human resources, budget and operational standard procedures in its implementation that need to be handled by the Sumedang District Police. Keywords: BTS Check Position, Information Technology, Fence